(3bdGFO GdYbHGf heMGSf GdQDSGA hGdbVGI hGdcJGH hGdCYjGfs - (3GHf NGbGf , CHh fUQ,J (B528 (3g` s ((3CUagGf s)
(3ChdgG (B:s
(3GdMeO ddg GdPi QGVi dfG GdHjGf s
(3BNQgG (B:s
(3hjegd GdcGaQ MceI ef Gddg hYdeG s
(3GfXQ (B" 385" (3JGQjNs
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B134 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B49s
Keywords: (3GdJGQjNs